Adherence and satisfaction in Argus II prosthesis users: a self determination theory model. (4th July 2022) - Khan, Mariam; Branham, Kari; Jayasundera, Kanishka T.; Khan, Naheed W.
ABSTRACT: Background: Self-determination theory (SDT) of human motivation was used to examine associations between different forms of motivation in Argus II retinal prosthesis users and their engagement and satisfaction with the Argus device. Materials and Methods: Nine subjects were administered: 1) a Situational Motivation Scale (SIMS) questionnaire to measure intrinsic motivation, identified regulation, external regulation, and amotivation, and 2) the Argus questionnaire (AQ) which was organized into 5 categories to measure 'Decision to get an Argus implant, ' 'Self-perception as an Argus user', 'Utility of Argus, ' 'Perceived competence, ' and 'Family support.' Spearman correlations ( rs ) were used to find associations between measures from SIMS and AQ. Results: Nine subjects completed both questionnaires. Statistically significant associations were observed between identified regulation and AQ items from categories: Decision to get Argus, Self-perception, Utility of Argus, and Perceived competence; and between intrinsic motivation and AQ items from Self-perception and Utility. External regulation was negatively associated with Family support, and amotivation was associated with one item from Self-perception. Engagement with the device and satisfaction were associated to both identified regulation and intrinsic motivation. There was no significant relationship between external regulation and adherence to the device. Conclusions: The SDT model can be used to investigate the types of motivation that influence uptake and engagement of the Argus device. Clinicians can use this knowledge to improve outcomes by supporting confidence in users and by encouraging them to maintain internalization and continued commitment to adherence.